Academic library data from the United States : an examination of trends - Budd, John M. (2021)
There is no doubt that there have been changes in recent years in academic libraries, their institutions, and the behaviors of their users. The literature in librarianship offers opinions and forecasts on a number of trends in services, resources, and personnel within libraries. Writings outside of librarianship also offer ideas about libraries and scholarship. The trends can be examined in the context of data reported by libraries. Data collected by the U.S. National Center for Education Statistics provide the opportunity for the analysis of a number of academic library service, collection and access, and personnel matters. Since the analysis can take into account changes over time, an integrated and holistic examination can be conducted.